Teaching of Orthography: From a Rough Road to an Investigative and Psychosociolinguistic Experience - Corredor Tapias, Joselyn; Romero Farfán, César (Universidad Pedagógica y Tecnológica de Colombia, 2020)
Initially, some reflections are exposed in which the problem situation is contextualized and posed: psychosociolinguistic learning of orthography; later, the investigative experience of this paper authors is shared, in relation to the development of a pedagogical proposal to achieve the correct use of the accent mark in Spanish, with two groups of infants, of the same number of educational institutions, from two municipalities of Boyaca state, and, finally, linguistic, grammatical, sociolinguistic, psychosociolinguistic, lexical and contextual elements, among others, related to spelling are presented.